Using design patterns in the development of a planner-based courseware system - Al-Tahat K.S.; Sembok T.M.T.; Idris S.B. (2023)
Design patterns have received a lot of attention recently, especially from the object-oriented community as a technique for design reuse. It has proved itself as an important piece that was missing from object-oriented design methods. Design patterns make it easier to reuse successful designs and architectures by providing solutions to common design problems at the abstract level. We have adopted an object-oriented development method complemented with design patterns in the development of a multimedia courseware system. The adoption of design patterns has helped us reuse software architectures and successful design experiences of design experts. In the system architectures, some design patterns are used only once, while others are used more than once in different places. This paper introduces some uses of design patterns in the design of a multimedia courseware system to obtain a flexible and reusable architecture as well as some of our experience in applying design patterns and some points that we think should pay attention to.